1997
DOI: 10.1002/(sici)1096-8628(19971003)72:1<71::aid-ajmg15>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Growth and growth hormone therapy in children with achondroplasia: A two-year experience

Abstract: The efficacy and safety of recombinant human growth hormone (hGH) administration was studied in children with achondroplasia. Fifteen children with achondroplasia, seven boys (4.8-12.2 years of age) and 12 girls (5.7-2.2 years of age), were treated daily with hGH at a dosage of 1 IU/kg/week. Auxological assessments were performed 6 months before, at initiation of, and at 6, 12, and 24 months following initiation of growth hormone (GH) therapy. Before initiating GH therapy, hypothalamic-pituitary and thyroid fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Likewise, in the study of Tanaka et al and Stamoyannou et al, relative sitting height was not significantly changed during the study period, but the ratio of lower limb length to height was significantly increased, i.e. improved [8,9]. In the evaluation of 145 treated individuals by Seino et al, an improvement of leg-to-height ratio, from 37.6% to 39.1% following the first year of treatment, was found [10].…”
Section: Change In Body Proportions During Gh Treatmentmentioning
confidence: 83%
See 1 more Smart Citation
“…Likewise, in the study of Tanaka et al and Stamoyannou et al, relative sitting height was not significantly changed during the study period, but the ratio of lower limb length to height was significantly increased, i.e. improved [8,9]. In the evaluation of 145 treated individuals by Seino et al, an improvement of leg-to-height ratio, from 37.6% to 39.1% following the first year of treatment, was found [10].…”
Section: Change In Body Proportions During Gh Treatmentmentioning
confidence: 83%
“…Already in 1933, in Denmark, a treatment experiment was done using pituitary extracts in a patient with chondrodystrophy (presumably achondroplasia) [5]. Several studies since the introduction of recombinant growth hormone have reported short-term (up to 2 y) treatment data on smaller groups of children with achondroplasia [6][7][8][9][10]. Only one study has reported on long-term treatment of these children [11].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 58 included studies, four were randomised control trials [ 22 , 32 , 53 , 54 ], 25 were retrospective case studies [ 5 , 23 25 , 27 , 28 , 30 , 34 , 35 , 39 , 41 , 42 , 45 , 46 , 48 , 49 , 57 , 59 , 65 69 , 71 , 73 ], 15 were retrospective cohort studies [ 20 , 21 , 26 , 29 , 31 , 36 , 38 , 40 , 47 , 55 , 58 , 60 , 61 , 70 , 74 ], eight were controlled before and after studies [ 15 , 51 , 52 , 56 , 62 64 , 72 ], two were prognostic studies [ 19 , 37 ], and one study was a non-randomised control trial [ 50 ]. There were three cross-sectional studies that used patient focused surveys [ 33 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Growth hormone plays an important role in regulating linear skeletal growth by promoting chondrocyte proliferation directly or indirectly through insulin-like growth factor-1. The majority of growth hormone trials in children with achondroplasia have been short-term [46][47][48][49][50][51][52]. These studies report an increase in growth velocity (65-75%) during the first year or a gain of 0.2-0.5 SD of height during the first year of treatment.…”
Section: Treatmentmentioning
confidence: 99%